2017
DOI: 10.1021/acsomega.7b00107
|View full text |Cite
|
Sign up to set email alerts
|

Graphene/Carbon Dot Hybrid Thin Films Prepared by a Modified Langmuir–Schaefer Method

Abstract: The special electronic, optical, thermal, and mechanical properties of graphene resulting from its 2D nature, as well as the ease of functionalizing it through a simple acid treatment, make graphene an ideal building block for the development of new hybrid nanostructures with well-defined dimensions and behavior. Such hybrids have great potential as active materials in applications such as gas storage, gas/liquid separation, photocatalysis, bioimaging, optoelectronics, and nanosensing. In this study, luminesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 62 publications
0
32
0
Order By: Relevance
“…These novel fullerene-based hybrid films are excellent candidate nanomaterials for potential application where graphene is already been studied such us gas/liquid separation [57], sensors [55,58], photovoltaics [86] or electronic devices [54]. Moreover, the different surface properties of the hybrid films are crucial for a plethora of bio-applications since the adsorption or the adhesion of cells or enzymes depends on the surface energy related to the wetting nature of the surface [87,88].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These novel fullerene-based hybrid films are excellent candidate nanomaterials for potential application where graphene is already been studied such us gas/liquid separation [57], sensors [55,58], photovoltaics [86] or electronic devices [54]. Moreover, the different surface properties of the hybrid films are crucial for a plethora of bio-applications since the adsorption or the adhesion of cells or enzymes depends on the surface energy related to the wetting nature of the surface [87,88].…”
Section: Discussionmentioning
confidence: 99%
“…This pressure was maintained throughout the deposition process. The hybrid Langmuir layers (ODA-GO) were transferred onto the Si-wafer substrates by horizontal dipping (Langmuir Schaefer technique), with downward and lifting speeds of 10 and 5 mm min À1 , respectively [47,57]. After the horizontal lift of a substrate, the ODA-GO film was dipped into an aqueous solution of fullerols (0.2 mg mL À1 ).…”
Section: Preparation Of Hybrid Multilayers Of Graphene Oxide and C 60mentioning
confidence: 99%
See 1 more Smart Citation
“…The third peak at 286.2 eV (9.0%) originates from the C-O-C epoxide/ether groups, whereas carbonyl functional groups (C=O) are associated with the peak at 287.3 eV (3.5%). Finally, the higher binding energy contribution recorded at 288.8 eV (1.7%) corresponds to the carboxyl groups (O-C=O) (Dimos et al, 2017;Kouloumpis et al, 2017;Tzitzios et al, 2017).…”
Section: Resultsmentioning
confidence: 96%
“…In Figure (a,b), it is observed that Raman spectra of both GO and CQD exhibits two peaks, at G band (1592 and 1582 cm −1 ) and D band (1347 and 1352 cm −1 ) of sp 3 and sp 2 hybridized carbon atoms, respectively. It reveals that the G‐band of GO is shifting toward higher frequencies (blue shift), this transition may refer to graphite amorphization and identical with the mechanically exfoliated graphene …”
Section: Resultsmentioning
confidence: 99%